Measurement of temperature excursions in different medication storage compartments during a mass casualty incident - Saskia Van Kemseke; Sofie Pauwels; Wilfried Cools; Ives Hubloue (Saudi Journal of Emergency Medicine)
Introduction: When a Mass Casualty Incident (MCI) or a disaster strikes, medication used on the scene is likely to be exposed to temperature excursions and variations. During MCIs/disasters pharmaceuticals are often not stored as recommended by the manufacturer. This could result in to a decreased stability of pharmaceuticals used on the scene and may result in treatment failure, especially when hazardous temperature excursions occur >30°C and >40°C. Aims/objectives: The main objective was to measure the magnitude of temperature excursions in medication storage compartments, how long they last and how often they occur during MCIs in Belgium. Materials/Methods: This observational study was conducted in Brussels (Belgium). The measurement period started in December 2020 and ended in August 2021. The measurements were done in 3 different simulation settings where medication is potentially stored at the time of an MCI, namely in an Advanced Medical Post (AMP), in the outdoor setting ("in the field") and in a fast car. In total, 17 temperature probes were used to measure temperatures in three medication storage compartments (metal, plastic, Emergency Medical Service or EMS bag). The definition of a significant temperature excursion was defined as a cumulative time above or below a certain cut-off of more than 24 hours per week. Results: Temperatures ( 25°C occurred for more than 50% of the time in June. Excursions in the different medication compartments in the outdoor setting occurred at the same time as inside the AMP. From the end of May till the end of the study period in August, significant temperature excursions >25°C follow each other repeatedly in the outdoor setting. This is also the case for excursions > 30°C, but much less pronounced. The fast care encountered significant temperature excursions above 25°C for more than 90% of the time between May and August. One significant excursion above 30°C took place during one week of June. Conclusion: For every simulation setting and every compartment, excursions below 24 hours per week). Especially when medication is stored in the field, hazardous temperature excursions (>30°C and even >40°C) occur. Every significant temperature excursion could lead to an altered pharmaceutical stability and thus to therapy failure. In order to evaluate drug stability after a significant temperature excursion, further pharmaceutical stability studies are necessary to prove this, especially of time- and temperature sensitive pharmaceutical products (TTSPPs). [SJEMed 2024; 5(1.100): S80-S80]